2021
DOI: 10.1007/978-3-030-85610-6_41
|View full text |Cite
|
Sign up to set email alerts
|

Passphrases Beat Thermal Attacks: Evaluating Text Input Characteristics Against Thermal Attacks on Laptops and Smartphones

Abstract: We investigate the effectiveness of thermal attacks against input of text with different characteristics; we study text entry on a smartphone touchscreen and a laptop keyboard. First, we ran a study (N=25) to collect a dataset of thermal images of short words, websites, complex strings (special characters, numbers, letters), passphrases and words with duplicate characters. Afterwards, 20 different participants visually inspected the thermal images to attempt to identify the text input. We found that long and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Even if the order of the keys is unknown, it is possible to significantly reduce the search space, requiring fewer attempts to guess a password. Furthermore, our study and studies from prior work [1,3,4,23] have shown that the order of entries can be leaked within a certain time frame.…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…Even if the order of the keys is unknown, it is possible to significantly reduce the search space, requiring fewer attempts to guess a password. Furthermore, our study and studies from prior work [1,3,4,23] have shown that the order of entries can be leaked within a certain time frame.…”
Section: Introductionmentioning
confidence: 53%
“…While most previous work on thermal attacks considered smaller search spaces (e.g., 10 keys on an ATM keypad or a mobile touchscreen [1,3,4,23,31]), our work focuses on thermal attacks against keyboards, which are relatively understudied. In contrast to the work by Kaczmarek et al [13], our model is able to determine the order of entries by comparing the temperatures of the heat traces at the different keys and uses the information obtained from the thermal image to probabilistically decode multiple hypothesized passwords ranked by probability of correctness.…”
Section: How Our Work Advances State Of the Artmentioning
confidence: 99%
See 3 more Smart Citations